Wpływ bezpośrednich inwestycji zagranicznych na poprawę konkurencyjności regionu Podkarpacia - Sołek, Celina (Influence of Foreign Direct Investment on Improving the Competitiveness of Podkarpackie Region, 2006)
The article presents the role of foreign direct investment in improving the level of technology in the Podkarpackie province. The author attempts to show the positive impact of technology transfer that has been made to the region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 593-600